Kinetic of Disinfection reaction by Sodium Hypochlorite Solution - Abdul-Wahab, Majid I.; Namoos, Bashaer M. (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
The present studier aims to study the kinetic of reaction at different experimental conditions depending on coliform bacteria concentration and hypochlorite ion. The effects that had been investigated were different of sodium hypochlorite doses, contact time, pH and temperature (20, 29, 37) o C. The water samples were taken from Al-Wathba water treatment plant in Risafa side of Tigris River in Baghdad. The biological tests included the most probable number (M.P.N) for indicating the concentration of coliform bacteria with different contact times and the total plate count (T.P.C) for indicating the amount of colonies for general bacteria. The iodimetry method (chemical test) was used for indicating the concentration of hypochlorite ion with different contact times. Different models were examined to fit the experimental data including the kinetics power law (first and second order) and Selleck model. It was found that the Selleck model fitted well the experimental data in which degree of Selleck model was equal to two and the rate constants was 1.3791 x 10-5 L / (mole min) at 20o C, 3.0806 x 10-5 L / (mole min) at 29oC, and 5.738 x 10-5 L / (mole min) at 37o C.